A308 HNF4A ORCHESTRATES PHYSIOLOGICAL REGULATIONS FROM THE INTESTINE THROUGH INCRETINS - Girard, R (J Can Assoc Gastroenterol, 2018)
BACKGROUND: HNF4α is a transcription factor known to regulate the intestinal epithelium homeostasis. Since HNF4α is also involved in nutrient metabolism, we questioned its ability to regulate systemic physiology from its specific alteration in the intestine. Upon a conditional deletion of HNF4A from the intestinal epithelium, we evidenced a deficiency for incretins (GIP and GLP-1) that favors glycemic and fat metabolism improvements in a murine model. AIMS: To demonstrate how sensitive is the physiology to intestinal changes in expression of the transcription factor HNF4α and enteroendocrine-derived incretins. METHODS: Control and HNF4αΔ(IEC) mice were fed with a chow diet or a high fat diet (HFD: 45% calories from fat) for 14 weeks. Effect of HNF4α on GIP transcription was assessed by luciferase-reporter assays. The endocrine system components were measured by ELISA. Physiological parameters were measured using metabolic cage and indirect calorimetry. Gross intestinal absorption of calories was estimated by measuring residual fecal calories using a calorimeter bomb. Glucose (GTT) and Insulin tolerance test (ITT) were performed intraperitoneally with 2 mg/g and 0.75 mUI/g doses, respectively. RESULTS: HNF4αΔ(IEC) mice fed with either high fat or chow diet displayed lowered circulating GIP and GLP-1 levels as compared to controls. These observations were reminiscent to a reduction of GIP and GCG gene transcript levels in the intestine. Coincidently, HNF4α was able to regulate transcriptional activity of the GIP promoter. Despite incretins deficiency, HNF4αΔ(IEC) mice harbored similar weight gain, feeding behavior, intestinal calories absorption and most intriguingly, similar GTT as compared to controls. However, ITT resulted in faster blood glucose clearance in HNF4αΔ(IEC) mice suggesting better insulin sensitivity in this context. Since obesity links insulin resistance and type 2 diabetes, HNF4αΔ(IEC) and control mice were fed with HFD to study their sensitivity to obesity. Once again, HNF4αΔ(IEC) mice displayed similar feeding behavior and intestinal calories absorption, but significant reduced weight gains as compared to controls under HFD, indicative of a higher energy expenditure. In parallel, fat metabolism was investigated using indirect calorimetry and showed a higher lipid consumption profile occurring in HNF4αΔ(IEC) mice during the dark cycle. CONCLUSIONS: These data are the first to link HNF4α as a common transcriptional regulator for incretins. Incretins downregulation following the intestinal epithelial loss of HNF4α improved native insulin sensitivity under chow diet and improved fat metabolism under HFD. Therefore, our study emphasizes on the key role of the intestinal epithelium and enteroendocrine function in nutrients metabolism following absorption and their impact on whole physiology. FUNDING AGENCIES: CIHR